(untitled) (Revista Contexto & Educação, 2025)
The aim of this article is to present the results of a model of intervention program to promote professional resilience in social educators. The intervention was elaborated with the association of the Ecological Engagement and the Experiential Methodology. Ten workers participated in 4 thematic modules. The analyses of the results were carried out based on the principles of Grounded Theory and the support of Atlas.ti. The analyses of the meetings focused on three main points: Institutional Routine, Interpersonal Communications and Care Practices. There was also an increase in positive expectations and confidence in children and adolescents’ future projects with more joy and affection in the relationships, as well as more efficient patterns of communication with the residents. These are protective factors in the institutional context that are essential components of professional resilience.